Food security in HIV/AIDS response: Insights from Homa Bay, Kenya - Dipankar Datta; James Njuguna (Taylor & Francis Group, 2009)
This paper examines the viability and effectiveness of a pilot farming initiative in reversing impacts of HIV/AIDS on the most affected households in Homa Bay, Kenya. The paper argues that once patients are stable, they can effectively be engaged in farming with minimal financial and technical support, resulting in enhanced food security of the affected households. More importantly, it helps to reduce HIV/AIDS-related stigma and improve the individual's self-esteem. Some of the key challenges of the pilot initiative were the limited number of agricultural extension workers and absence of facilities to enable them to deliver services to the farmers, the high cost of farm inputs, the unavailability of farm inputs when they were needed, poorly developed agricultural markets, and the absence of irrigation facilities. The paper recommends the sensitive scaling-up of this approach. However, farming initiatives by HIV/AIDS service NGOs should be linked to at least three key aspects: (a) treatment, care and support to HIV/AIDS affected households; (b) micro grant schemes or subsidies to enable farmers to purchase farming tools and farm inputs; and (c) comprehensive on-farm training support. To ensure effectiveness and wider reach, government needs to view agriculture through an HIV lens and promote a multisectoral approach that recognises the relationship between HIV/AIDS and food security. A number of immediate actions are required to strengthen this relationship, such as increased public investment to augment extension services, subsidise farm inputs, and develop infrastructure including agricultural markets.